2010
DOI: 10.1093/geronb/gbq046
|View full text |Cite
|
Sign up to set email alerts
|

Use of Spoken and Written Japanese Did Not Protect Japanese-American Men From Cognitive Decline in Late Life

Abstract: We did not find evidence to support the hypothesis that multilingualism is associated with cognitive reserve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 38 publications
3
54
0
Order By: Relevance
“…This discrepancy might be caused by the self-reported and less accurate questionnaire about physical activities we utilized. Hypertension, type 2 diabetes, smoking, and urban living environment were not correlated with age at AD onset, which is similar to the results of other studies [5, 7, 23, 24]. …”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This discrepancy might be caused by the self-reported and less accurate questionnaire about physical activities we utilized. Hypertension, type 2 diabetes, smoking, and urban living environment were not correlated with age at AD onset, which is similar to the results of other studies [5, 7, 23, 24]. …”
Section: Discussionsupporting
confidence: 90%
“…The interpretation of the protective effect of bilingualism against AD is that the use of two languages can enhance cognitive reserve (CR) by switching between the two languages, and increasing the efficiency of the executive control system [4]. However, inconsistent results have been reported in other studies [5-7], which demonstrated that the age of dementia diagnosis was not significantly different between bilinguals and monolinguals. The potential reasons for the contradictory findings suggested by Calvo et al [8] were methodological differences in the definition of bilingualism, the sample design, the definition of age of onset, and the consideration of other variables known to affect CR.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This uneven distribution of item difficulties has been shown to cause biased estimates of rates of decline (21). An increasingly popular and validated approach to minimize this bias is the use of item response theory (IRT) to score global cognition data to establish linearity in the scale (22,23). Because analyses using the IRT scores provide a more statistically robust estimate of the associations evaluated, such results are more likely to estimate the true underlying association.…”
Section: Item Response Theorymentioning
confidence: 99%
“…17,[19][20][21] However, despite a large number of studies that support the concept of cognitive reserve, [22][23][24] other studies have found little or no support for it. [25][26][27][28] Albeit, studying cognitive reserve is difficult because there are different methods of how it is measured (ie, cognitive changes over time; from a cross-sectional sample, subtracting a standardized measure of a fluid ability from a standardized measure of crystallized ability) and different assumptions of what affects it (ie, does the amount of education predict it or does the quality of that education matter?). So the reader should keep these methodological issues in mind when interpreting the results of studies examining cognitive reserve.…”
Section: Introductionmentioning
confidence: 99%